Pengaruh Komunikasi Pelayanan dan Kepuasan terhadap Loyalitas Pelanggan di 7-Eleven Buaran - Logahan, Jerry Marcellinus; Putri, Yohana Tiara Eka (Binus Business Review, 2013)
This research was motivated by low communication in the business retail in terms of service from employees to customers. It influences the decline in customer satisfaction and leads to customer loyalty at a very low level. This study aims to identify and analyze the significance of the influence of customer service (X1) and customer satisfaction (X2) on customer loyalty (Y). Research was conducted in February - May 2013 held at 7-Eleven Buaran Jakarta. Research used quantitative method by using questionnaires filled directly by the visitors of 7-Eleven Buaran with a population of 19.920 people and a sample of 100 people, calculated using the Slovin formula. Validity test, reliability, normality, correlation, regression, hypothesis, and the determination carried out in this study using the data processed using SPSS (Statistical Product and Service Solutions) version 16.0. Results indicated that customer service has significant influence by 14.6% on customer loyalty, customer satisfaction has a significant effect of 8.5% on customer loyalty, and customer service and customer satisfaction have significant influence amounted to 15,2%. Thus, this study showed that customer service and customer satisfaction have a significant effect on customer loyalty in 7-eleven Buaran Jakarta.